Insults and death threats against Nadiya Lazzouni from a forensic linguistics perspectives - Zahra, Fattin Nayla; Santoso, Wahyudi Joko; Wijaya, Ayudhia Ratna (Comparative Legilinguistics, 2025)
This paper presents a comprehensive forensic linguistic analysis of insults and death threats directed at Nadiya Lazzouni, emphasizing the roles of semantics, pragmatics, and sociolinguistics within legal contexts. Utilizing a mixed-methods approach, the study combines qualitative and quantitative analyses to examine linguistic elements within legal frameworks, drawing on data from Lazzouni’s personal social media account, where she disclosed the threatening letter. Through a comparative legilinguistics perspective, the research elucidates how various legal systems interpret and enforce laws related to hate speech and threats. The findings reveal that the letter contains severe insults and death threats rooted in religious and racial identity, underscoring the legal challenges posed by multilingual and sociocultural variations in legal interpretation. This study highlights the necessity for standardized legal terminology and the development of forensic linguistic tools to enhance clarity and fairness in legal proceedings involving speech-related offenses. By integrating linguistic analysis with forensic and comparative legal methodologies, this research contributes to the broader discourse on multilingualism in legal practice and the effectiveness of legal communication in addressing hate speech and threats.